2011
DOI: 10.1021/la200917y
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Mechanism for the Enhanced Ability of Lipid Membrane Penetration of Polyarginine

Abstract: Arginine-rich, cell-penetrating peptides (e.g., Tat-peptide, penetratin, and polyarginine) are used to carry therapeutic molecules such as oligonucleotides, DNA, peptides, and proteins across cell membranes. Two types of processes are being considered to cross the cell membranes: one is an endocytic pathway, and another is an energy-independent, nonendocytic pathway. However, the latter is still not known in detail. Here, we studied the effects of the chain length of polyarginine on its interaction with an ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 63 publications
4
59
0
Order By: Relevance
“…S5 in supplementary material. The conjugation of octaarginine peptide has been shown previously [2,31,39,53] to enhance cellular uptake of metal complex dyes without the requirement for membrane permeablization and this is further exemplified here in both cell lines. Dye uptake was measured by live-cell time course analysis and quantified by measuring the dye intensity in each cell type at the same time points after incubation wherein the concentration of each dye applied to the cell medium was identical.…”
Section: Electrochemistrymentioning
confidence: 66%
“…S5 in supplementary material. The conjugation of octaarginine peptide has been shown previously [2,31,39,53] to enhance cellular uptake of metal complex dyes without the requirement for membrane permeablization and this is further exemplified here in both cell lines. Dye uptake was measured by live-cell time course analysis and quantified by measuring the dye intensity in each cell type at the same time points after incubation wherein the concentration of each dye applied to the cell medium was identical.…”
Section: Electrochemistrymentioning
confidence: 66%
“…In de novo designed AMPs, Arg and Lys are popular choices, as they are protonated under physiological conditions. Although both amino acids have comparable charge and Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/27/15 1:57 AM hydrophobicity, Lys primary amine interacts less electrostatically with PLs than the Arg guanidium group, which could explain the stronger binding affinity of Arg-containing peptides to lipid membranes than that of Lys-containing counterparts (65)(66)(67).…”
Section: Improvement Of Antimicrobial Potency and Cell Selectivity Chmentioning
confidence: 99%
“…ITC measurements on different CPPs reported binding affinities in the M range that were enthalpically favored and associated with positive heat capacities indicating that electrostatics are important for the interaction [27][28][29][30][31][32]. Using calorimetry, plasmon resonance and fluorescent studies, the presence of negatively charged lipids was shown to be essential or to increase the affinity of TAT [33][34][35], oligoarginine peptides [27]; [29,30,31,35] and also of penetratin [36,[37][38][39][40]; [28]. Plasmon waveguide resonance (PWR) studies have reported an increase of ~20-100 fold in affinity when anionic lipids where included in the membrane [38].…”
Section: Binding To Lipidsmentioning
confidence: 99%